(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Statistical modeling is utilized effectively to development relation/s between the dependent variables and independent variables. In other words, it describes how one or more random variables are related to one more other variables. Building verified models can help in predicting performance characteristics, and saving time and money. This study aims to present a statistical models which help to understand the significance of the different parameters in characterizing the performance of the Thin Asphalt Overlay (TAO). The experimental program included: design the thin asphalt overlay mixtures using one gradation type (9.5 Nominal Maximum Aggregate Size NMAS), three filler types (conventional mineral filler, Ordinary Portland Cement, and Quick lime), and five percentages of asphalt content to identify the optimum asphalt content. Then, Styrene Butadiene Styrene (SBS) modified polymer binder was introduced for performance enhancement. Performance tests were used to evaluate TAO mixture in term of some main namely, volumetric, mechanical, and durability properties are (bulk density, indirect tensile strength and tensile strength ratio). Statistical Product and Service Solutions (SPSS) software (Version 24) was used as a tool for models building. To find the most accurate statistical models, linear and nonlinear regression was achieved. This study demonstrates that the using statistical modeling is achievable and offer a vital tool to describe the characteristics and performance of the TAO mixture in term volumetric, mechanical and durability properties.